Art, global Maoism and the Chinese cultural revolution - Galimberti, Jacopo 1981-; Haro García, Noemi de; Scott, Victoria H. F. (Manchester University Press, 2020)
This is the first book to explore the global influence of Maoism on modern and contemporary art. Featuring eighteen original essays written by established and emerging scholars from around the world, and illustrated with fascinating images not widely known in the west, the volume demonstrates the significance of visuality in understanding the protean nature of this powerful worldwide revolutionary movement. Contributions address regions as diverse as Singapore, Madrid, Lima and Maputo, moving beyond stereotypes and misconceptions of Mao Zedong Thought's influence on art to deliver a survey of the social and political contexts of this international phenomenon. At the same time, the book attends to the the similarities and differences between each case study. It demonstrates that the chameleonic appearances of global Maoism deserve a more prominent place in the art history of both the twentieth and twenty-first centuries
Keywords: Maoismus -- Motiv; Maoismus; Kunst; Mao, Zedong / 1893-1976 / Influence; Communism and art; Mao, Zedong / 1893-1976; Influence (Literary, artistic, etc.); Aufsatzsammlung